(untitled) (REMUNOM, 2024)
The sun, a source of light for the planet, is extremely important for the maintenance of human’s, animal’s and plant’s lives, and it is classified in visible light, infrared and ultraviolet radiation. UV rays are around 3 to 5% of the solar emission that reaches Earth and, despite their great importance, excessive exposure to this radiation, without adequate protection, can lead to several negative consequences for humans. Sunscreens emerged when it society realized that some substances have photoprotective properties and are capable of preventing such consequences. These substances may originate from medicinal plants, such as Melaleuca alternifolia, whose essential oil has anti-inflammatory, antioxidant and analgesic properties. This work aims to evaluate the in silico and in vitro solar photoprotection factor of Melaleuca alternifólia’s essential oil. This study was made trough a spectrophotometry test of the oil, evaluating the biological activities of its main component. The results showed positive FPS values, as determined by ANVISA, and probability of radioprotective and antioxidant activity. It was concluded that Melaleuca alternifolia’s essential oil has good photoprotective potential.